2010
DOI: 10.1158/1078-0432.ccr-09-1555
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Gemcitabine Metabolic Genes and Pancreatic Cancer Survival and Drug Toxicity

Abstract: Purpose: To show whether single nucleotide polymorphisms (SNP) of drug metabolic genes were associated with toxicity of 2′,2′-difluoro 2′-deoxycytidine (gemcitabine)-based chemoradiotherapy and overall survival (OS) of patients with pancreatic cancer.Experimental Design: We evaluated 17 SNPs of the CDA, dCK, DCTD, RRM1, hCNT1, hCNT2, hCNT3, and hENT1 genes in 154 patients with potentially resectable pancreatic adenocarcinoma who were enrolled in clinical trials at The University of Texas M.D. Anderson Cancer C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 29 publications
1
66
1
Order By: Relevance
“…However, most of our studies were limited by small sample sizes, small numbers of genes examined, and lack of validation and unknown functional significance of the genetic variants [2][3][4][5]. Thus, the potential value of our previous findings in clinical application is not yet known.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, most of our studies were limited by small sample sizes, small numbers of genes examined, and lack of validation and unknown functional significance of the genetic variants [2][3][4][5]. Thus, the potential value of our previous findings in clinical application is not yet known.…”
Section: Introductionmentioning
confidence: 97%
“…We have shown previously that genetic variations in drug metabolism and DNA repair correlate with overall survival (OS) of patients with pancreatic cancer [2][3][4][5]. However, most of our studies were limited by small sample sizes, small numbers of genes examined, and lack of validation and unknown functional significance of the genetic variants [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact other studies have not found an association between this CDA Lys 27 Gln polymorphism and treatment outcome after treatment with nucleoside analogs. 5,6 One limitation of our study is the absence of more detailed information on the individual events and frequencies contributing to the severe hematological toxicity, including whether or not they were asymptomatic or contributed to dose modification or treatment delay.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, other data does not find an association between this CDA polymorphism and treatment outcome with gemcitabine. 5,6 The Radiation Therapy Oncology Group (RTOG) 9704 study is a phase III randomized post-operative adjuvant study in patients after resection of pancreatic cancer comparing pre-and post-chemoradiation 5-FU with preand post-chemoradiation 5-fluororuacil and gemcitabine. 7 It represents a unique tool to validate markers predictive of gemcitabine treatment response and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Data regarding toxicity related to CDA polymorphisms are inconsistent (16)(17)(18). Nevertheless, several studies demonstrated that single nucleotide polymorphism (SNP) of CDA c.79 A>C, c.208 G>A and c.435C>T, with resulting decreased serum CDA concentration, may lead to severe toxicity induced by GCB (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%